Food restriction reconfigures naïve and learned choice behavior in Drosophila larvae. (2nd January 2020) - Brünner, Benita; Saumweber, Juliane; Samur, Merve; Weber, Denise; Schumann, Isabell; Mahishi, Deepthi; Rohwedder, Astrid; Thum, Andreas S.
Abstract: In many animals, the establishment and expression of food-related memory is limited by the presence of food and promoted by its absence, implying that this behavior is driven by motivation. In the past, this has already been demonstrated in various insects including honeybees and adult Drosophila . For Drosophila larvae, which are characterized by an immense growth and the resulting need for constant food intake, however, knowledge is rather limited. Accordingly, we have analyzed whether starvation modulates larval memory formation or expression after appetitive classical olfactory conditioning, in which an odor is associated with a sugar reward. We show that odor-sugar memory of starved larvae lasts longer than in fed larvae, although the initial performance is comparable. 80 minutes after odor fructose conditioning, only starved but not fed larvae show a reliable odor-fructose memory. This is likely due to a specific increase in the stability of anesthesia-resistant memory (ARM). Furthermore, we observe that starved larvae, in contrast to fed ones, prefer sugars that offer a nutritional benefit in addition to their sweetness. Taken together our work shows that Drosophila larvae adjust the expression of learned and naïve choice behaviors in the absence of food. These effects are only short-lasting probably due to their lifestyle and their higher internal motivation to feed. In the future, the extensive use of established genetic tools will allow us to identify development-specific differences arising at the neuronal and molecular level.